2020
DOI: 10.1101/2020.07.23.20160424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Retrospective Study on Efficacy and Safety of Guduchi Ghan Vati for Covid-19 Asymptomatic Patients

Abstract: Background Coronavirus disease 2019 (Covid-19) has been declared global emergency with immediate safety, preventative and curative measures to control the spread of virus. Confirmed cases are treated with clinical management as they are diagnosed but so far, there is no effective treatment or vaccine yet for Covid-19. Ayurveda has been recommended by preventative and clinical management guidelines in India and several clinical trials are ongoing. But there is no study to assess impact of Ayurveda on Covid-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The reported efficacy of favipiravir, lopinavir/ritonavir and remdesivir was found to be either similar or inferior to the natural component from Guduchi. A previous retrospective study 21 also found that Guduchi Ghan Vati was effective in viral clearance and reducing hospital stay compared to standard care.…”
Section: Introductionmentioning
confidence: 81%
“…The reported efficacy of favipiravir, lopinavir/ritonavir and remdesivir was found to be either similar or inferior to the natural component from Guduchi. A previous retrospective study 21 also found that Guduchi Ghan Vati was effective in viral clearance and reducing hospital stay compared to standard care.…”
Section: Introductionmentioning
confidence: 81%
“…As on July 14, 2020, 25% of the total 312 Indian clinical trials registered with CTRI involved Ayurveda, Yoga and Naturopathy [61]. While the results of some of these trials (such as [45,40]) indicate positive results for Ayurvedic formulations, most of these trials restrict to studying the impact of one formulation on the entire patient population without following the true Ayurvedic approach of personalized medicine. This severely limits the potential benefits that Ayurvedic and Yogic sciences have to offer for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…They also offer specific guidelines about treatment and management of diseases that spread during Janapadoddhvansa. Based on this, many proposals to use Ayurveda for prophylaxis [20,21,22,23,24,25,26,27,28,29,30,31,32,33] as well as treatment of COVID-19 [34,22,35,36,37,23,24,25,27,38,28,39,40,41,42,43] have been published. See [44] (Related Works) for a detailed review on use of Yoga, Ayurveda and other systems of traditional medicine for treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted to understand the COVID-19 pandemic and the conditions posed by it from the perspective of Ayurveda [77,46,68,22,76,101,60]. Based on these observations and the study of classical Ayurveda texts, several experts have proposed the use of Ayurveda for prophylactic [104,78,75,24,71,66,80,62,44,57,48,100,50,102] as well as therapeutic use [83,75,73,109,105,24,71,66,62,21,44,39,49,101,72,85] in COVID-19. Some studies have also suggested that lifestyle modifications, such as immunity boosting food, can aid in fighting the current situation [4].…”
Section: Related Workmentioning
confidence: 99%